Implementation of the Jigsaw Model to Increase Student Activeness in History Learning in Class X Senior High School of SMA YPST Porame - Tresya Claudia Sawane; Lukman; Haliadi; Iskandar; Ismail (Kirana Publisher (KNPub), 2026)
The results of this study consist of: (1) how the jigsaw model is implemented in Class X of YPST Porame High School, (2) how the students' activeness in history learning is in Class X of YPST Porame High School, (3) why the jigsaw model in history learning can increase the activeness of students in Class X of YPST Porame High School. Based on these problems, this study aims to (1) explain the jigsaw model in Class X of YPST Porame High School, (2) describe the activeness of students in history learning in Class X of YPST Porame High School, (3) analyze the implementation of the jigsaw model in history learning can increase the activeness of students in Class X of YPST Porame High School. This research method uses a descriptive qualitative research method, data collection techniques through observation, interviews, and documentation methods. The subjects of this study consisted of history teachers and students in Class X of YPST Porame High School. Data were analyzed through the stages of data reduction, data presentation, as well as drawing conclusions and verification. Based on the results of this study, it shows that the implementation of the jigsaw model in Class X SMA YPST Porame: (1) is able to create an active, collaborative, and enjoyable learning atmosphere, (2) Students are directly involved in the learning process through discussions, presentations, and group work, as well as responsibility for the material being studied, (3) Teachers act as facilitators who guide and motivate students during the learning process. The jigsaw model research has been proven to increase the activeness and quality of history learning in Class X SMA YPST Porame.